2020
DOI: 10.1038/s41598-020-70907-0
|View full text |Cite
|
Sign up to set email alerts
|

Topographical curvature is sufficient to control epithelium elongation

Abstract: How biophysical cues can control tissue morphogenesis is a central question in biology and for the development of efficient tissue engineering strategies. Recent data suggest that specific topographies such as grooves and ridges can trigger anisotropic tissue growth. However, the specific contribution of biologically relevant topographical features such as cell-scale curvature is still unclear. Here we engineer a series of grooves and ridges model topographies exhibiting specific curvature at the ridge/groove … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The difference between f -CTs and t -CTs might originate from different cell-substrate interactions due to different curvatures. Previous investigations have demonstrated that cell scale curvature could affect focal adhesion (FA) organization and dynamics ( 43 ), which would profoundly influence pluricellular protrusion orientations ( 44 ) and cell polarity ( 45 ). In our case, it was possible that t -CTs and f -CTs responded to distinct curvatures with different tissue organizations and mechanics.…”
Section: Resultsmentioning
confidence: 99%
“…The difference between f -CTs and t -CTs might originate from different cell-substrate interactions due to different curvatures. Previous investigations have demonstrated that cell scale curvature could affect focal adhesion (FA) organization and dynamics ( 43 ), which would profoundly influence pluricellular protrusion orientations ( 44 ) and cell polarity ( 45 ). In our case, it was possible that t -CTs and f -CTs responded to distinct curvatures with different tissue organizations and mechanics.…”
Section: Resultsmentioning
confidence: 99%
“…They seem to sense curvature through cell thickness, tissue density and nuclear shape and position, and respond by subsequent change in the localization of YAP (lower in high density regions), expression of nuclear lamins and proliferation rate. Cell localization within a migrating epithelial monolayer (leader vs. mid-cluster), as well as the size of the cell cluster [99] and curvature magnitude [100] all affect F-actin and nuclear positioning, excluding both from highly convex regions [100]. Longitudinal groove scaffolds also help orient monolayer growth [100].…”
Section: Scaffoldingmentioning
confidence: 99%
“…Cell localization within a migrating epithelial monolayer (leader vs. mid-cluster), as well as the size of the cell cluster [99] and curvature magnitude [100] all affect F-actin and nuclear positioning, excluding both from highly convex regions [100]. Longitudinal groove scaffolds also help orient monolayer growth [100]. The intestinal epithelium senses curvature, as well.…”
Section: Scaffoldingmentioning
confidence: 99%
“…[7] In this context, the in vivo environment surrounding or associated with the epithelia are edgeless and exhibit fibrillar and curved topographies on the cellular scale. [10] Furthermore, due to the use of synthetic polymer-based materials, these templates exclude ECM remodeling or proteolytic degradation mediated by matrix metalloproteinases to navigate through confined spaces. [11] Therefore, fibrillar and edge-less topographies are needed to investigate cell migration in the context of cell contact-guidance and morphogenesis.…”
Section: Introductionmentioning
confidence: 99%